In everyone's home (Journal of Parents and Teachers, 2026)
Marisol Garrido analyses how, through five sectors that study different factors,the family environment influences children's lives. She also highlights the importance ofthe family-school relationship. She draws attention to the influence of the family onchildren's growth and development.
Keywords: Family, Education, Development and Environment